Bibliometric analysis of the field of green public procurement - Simona Roxana Patarlageanu; Mihai Dinu; Marius Constantin (Amfiteatru Economic Journal, 2020)
Sustainability and sustainable development are objectives, but also values that must be respected in the field of public procurement. The main objective of this paper is to document the interest in the research area of green public procurement. The research methodology involves the elaboration of a bibliometric analysis (therefore a quantitative research method), in the form of an inventory of the publication activity in the aforementioned field. The analysis was developed by querying the existing database on the Scopus platform, which contains documentation on journals, scientific papers, books and others. The query determined the display of a number of 6,257 scientific documents existing in the database containing the acronym for Green Public Procurement in the title, summary or keywords. The query was conducted on September 25, 2019 and includes publications, regardless of the location or date of publication. The research results confirm the increase of the scientific interest in the field of green public procurement. Since 2010 until the moment of querying the Scopus database, 3,441 documents were identified related to this topic, which represents more than half of the total elaborated documents existing in the database on the same topic, indexed between 1959 and 2009.
Keywords: Q57; 330; green public procurement; environmental policy; bibliometric analysis; VOSviewer